GAMBARAN GULA DARAH PADA LANSIA DI PANTI SOSIAL TRESNA WREDHA WANA SRAYA DENPASAR DAN PANTI SOSIAL WREDHA SANTI TABANAN: DESCRIPTION OF BLOOD SUGAR IN ELDERLY IN NURSING HOME WANA SRAYA DENPASAR AND IN NURSING HOME SANTI TABANAN - Putra, I Gede Yudiana (Stikes Wira Medika Bali, 2019)
DESCRIPTION RANDOM BLOOD SUGAR IN ELDERLY IN SOCIAL INSTITUTION ELDERLY WANA SRAYA DENPASAR AND THE SOCIAL INSTITUTION ELDERLY SANTI TABANAN Yudiana Putra, IGStudy Program DIII of Nursing, Nursing Academy of Kesdam IX/Udayanayudianakesdam@gmail.com ABSTRACTBackground: Disease that is often found in the elderly is diabetes mellitus. Diabetes mellitus is characterized by chronic hyperglycemia due to work effects or insulin secretion. If diabetes mellitus cannot be treated, it can help overcome complications that can worsen health.Objective: This study aims to determine the description of random blood sugar at the elderly in in social institution elderly wana sraya denpasar and the social institution elderly santi tabanan.Method: The study design used descriptive method. The research location at social institution elderly wana sraya denpasar and the social institution elderly santi tabanan. Total population of 50 respondents, with 11 respondents did not meet the criteria so that there were 39 respondents. The research instrument was an observation sheet, Easytouch tool and blood sugar sticks to measure random blood sugar. Data processing is done using computerization. Data is presented in a textual and is accompanied by a table.Results: Measurement of random blood sugar showing 24 respondents (61.54%), with uncertain DM category (100-199 mg / dl); 11 respondents (28.21%) with non-DM categories (<100 mg / dl), while 4 respondents (10.25%) showed DM categories (> 200 mg / dl). The average value of blood sugar at 39 respondents was 140.025 mg/dl.Conclusion: Most of the elderly showed the results of random blood sugar with the category of uncertainty for DM as many as 24 respondents, with a range of examination results 100-199 mg / dl. Keywords: Random Blood Sugar, Elderly, Descriptive